Transformers, dark of the moon - LaBeouf, Shia, 1986-; Duhamel, Josh, 1972-; Turturro, John, 1957-; Tyrese; Huntington-Whiteley, Rosie, 1987-; Dempsey, Patrick, 1966-; Dunn, Kevin, 1956-; White, Julie, 1961-; Malkovich, John.; McDormand, Frances; Murphy, Don, 1966-; DeSanto, Tom.; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2011)
The Autobots learn of a Cybertronian spacecraft hidden on the moon and race against the Decepticons to reach it and to learn its secrets.
DVD, widescreen, NTSC; Dolby Digital 5.1.
English, French or Spanish dialogue; English, French or Spanish subtitles; English audio description.
Shia LaBeouf, Josh Duhamel, John Turturro, Tyrese Gibson, Rosie Huntington-Whiteley, Patrick Dempsey, Kevin Dunn, Julie White, John Malkovich, Frances McDormand.
MPAA rating: PG-13; for intense prolonged sequences of sci-fi action violence, mayhem and destruction, and for language, some sexuality and innuendo.
Keywords: Transformers (Fictitious characters) -- Drama; Robots -- Drama; Moon -- Drama; Imaginary wars and battles -- Drama; Robots -- Teatro; Luna -- Teatro; Guerras imaginarias -- Teatro; Feature films; Action and adventure films; Science fiction films; Video recordings for people with visual disabilities; Fiction films; Feature films; Adventure films; Science fiction films